Prevalence and Impact on Mechanical Ventilation Weaning of Pleural Effusion in ICU Patients. Issue 5 (September 2019) - Dres, Martin; Razazi, Keyvan
Abstract : Pleural effusion is frequently encountered in patients who are mechanically ventilated in the intensive care unit and may be logically suspected in case of difficult weaning from mechanical ventilation. Through several mechanisms, pleural effusion may impair gas exchange, respiratory mechanics, and ventilation/perfusion matching. However, data exploring the respective contribution of pleural effusion on weaning failure are scarce. This review discusses the most recent findings pertaining to the potential role of pleural effusion in weaning outcome.